The emotional surge: in-depth qualitative exploration of rumination and emotional turbulence in non-suicidal self-injurers - Khan, Soulat; Rehna, Tasnim; Butt, Tayyab Ali (Frontiers in Psychology, 2024)
Non-suicidal self-injury (NSSI) is an emerging pathological condition among emerging adults, causing significant distress and hindering daily life functioning. The increasing prevalence of NSSI highlights its importance as a crucial area requiring clinical attention. To devise effective interventions for managing NSSI, it is important to identify the factors contributing to its onset and maintenance. Therefore, the current study aims to explore emotional and cognitive factors to provide a holistic understanding of NSSI in emerging adults in the Pakistani context. For this purpose, a qualitative study was conducted using in-depth, semi-structured interviews with N = 10 self-injurers (mean age: 22.2 years) recruited through purposive sampling. Participants had engaged in self-injury at least five times in the past year without suicidal intent. The arm was identified as the most common site for self-injury, with cutting being the most frequently used method. Data from the transcribed interviews were analyzed using Braun and Clarke's reflexive thematic analysis. Three main themes—‘emotional turbulence,’ ‘low distress tolerance,’ and ‘rumination’—and nine subthemes emerged, highlighting the emotional and cognitive factors contributing to the initiation and maintenance of NSSI. The findings of this study provide valuable insights into the emotional and cognitive dimensions of NSSI in emerging Pakistani adults. These insights will aid in treatment planning and in selecting appropriate strategies for reducing and ultimately eradicating NSSI.